2010
DOI: 10.1111/j.1570-7458.2010.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and mixed infections with wild type and genetically modified Helicoverpa armigera nucleopolyhedrovirus on movement behaviour of cotton bollworm larvae

Abstract: Naturally occurring insect viruses can modify the behaviour of infected insects and thereby modulate virus transmission. Modifications of the virus genome could alter these behavioural effects. We studied the distance moved and the position of virus-killed cadavers of fourth instars of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) infected with a wild-type genotype of H. armigera nucleopolyhedrovirus (HaSNPV) or with one of two recombinant genotypes of this virus on cotton plants. The behavioural effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…BmNPV-infected silkworms showed enhanced locomotory behavior on the 4 dpi (Kamita et al, 2005), HearNPV-infected cotton bollworm (Georgievska et al, 2010) and LdMNPV-infected European gypsy moth (Hoover et al, 2011) all exhibited climbing behavior in the later stage after NPV infection. In previous studies, two NPV-encoded genes (ptp and egt) were found to be critical to the manipulated behavior of NPV-infected lepidopteran larvae (Hoover et al, 2011;Kamita et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…BmNPV-infected silkworms showed enhanced locomotory behavior on the 4 dpi (Kamita et al, 2005), HearNPV-infected cotton bollworm (Georgievska et al, 2010) and LdMNPV-infected European gypsy moth (Hoover et al, 2011) all exhibited climbing behavior in the later stage after NPV infection. In previous studies, two NPV-encoded genes (ptp and egt) were found to be critical to the manipulated behavior of NPV-infected lepidopteran larvae (Hoover et al, 2011;Kamita et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…HearNPV is one of the most widely used commercialized NPV products for the control of the devastating pest H. armigera in cotton and vegetable fields (Georgievska et al, 2010;Grzywacz et al, 2000). The pathogenicity of HearNPV declines when H. armigera larvae grow larger or the inoculation dose decreases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Toxin expression in baculovirus-infected larvae also results in larvae falling from their position on a plant and dying on the ground, while wild-type baculovirus-infected larvae tend to climb and die in a higher position on a plant [ 124 , 125 ]. The climbing behavior of baculovirus-infected larvae is thought to augment the distribution of progeny OBs from a cadaver and facilitate dissemination [ 126 ].…”
Section: Factors Involved In Successful Improvement Of Baculovirusmentioning
confidence: 99%
“…Although egt exists in nearly all lepidopteran baculoviruses, its role in baculovirus‐induced tree‐top disease may not be highly conserved. In Helicoverpa armigera , infection by the egt ‐negative virus of H. armigera single nucleopolyhedrovirus (HaSNPV) resulted in lower virus yield and faster time to death in fourth instars; however, there was no effect on the death positions of larvae under controlled glasshouse conditions or in field cages (Georgievska et al., ). Larvae of Trichoplusia ni and Spodoptera exigua that were infected with Autographa californica multiple nucleopolyhedrovirus (AcMNPV) also died at the same height as larvae infected with a mutant virus lacking the egt gene (Ros, van Houte, Hemerik, & van Oers, ).…”
Section: Introductionmentioning
confidence: 99%